2020
DOI: 10.1371/journal.pntd.0008547
|View full text |Cite
|
Sign up to set email alerts
|

An agonist of the CXCR4 receptor accelerates the recovery from the peripheral neuroparalysis induced by Taipan snake envenomation

Abstract: Envenomation by snakes is a major neglected human disease. Hospitalization and use of animal-derived antivenom are the primary therapeutic supports currently available. There is consensus that additional, not expensive, treatments that can be delivered even long after the snake bite are needed. We recently showed that the drug dubbed NUCC-390 shortens the time of recovery from the neuroparalysis caused by traumatic or toxic degeneration of peripheral motor neurons. These syndromes are characterized by the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…In this model, a sub‐lethal amount of α‐Latrotoxin (a pore‐forming neurotoxin from the black widow spider) or SPANs (Snake PLA 2 neurotoxins) locally injected in the mouse hind limb induces a rapid Ca ++ ‐mediated degeneration of motor axon terminals. Strikingly, nerve terminal degeneration is fully reversible, and motor axon terminals completely recover both structurally and functionally in a few days (Duregotti et al, 2015b , 2015c ; Negro et al, 2017 ; Stazi et al, 2020 ). By this toxin‐based experimental model, one can monitor the time course of morphological changes of PSCs, the activation of specific intracellular signaling pathways, and the effects of their manipulation on the recovery of motor function.…”
Section: Methods To Study Schwann Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this model, a sub‐lethal amount of α‐Latrotoxin (a pore‐forming neurotoxin from the black widow spider) or SPANs (Snake PLA 2 neurotoxins) locally injected in the mouse hind limb induces a rapid Ca ++ ‐mediated degeneration of motor axon terminals. Strikingly, nerve terminal degeneration is fully reversible, and motor axon terminals completely recover both structurally and functionally in a few days (Duregotti et al, 2015b , 2015c ; Negro et al, 2017 ; Stazi et al, 2020 ). By this toxin‐based experimental model, one can monitor the time course of morphological changes of PSCs, the activation of specific intracellular signaling pathways, and the effects of their manipulation on the recovery of motor function.…”
Section: Methods To Study Schwann Cellsmentioning
confidence: 99%
“…This transcriptome revealed that PSCs express the chemokine CXCL12α in response to injury, which, by engaging the CXCR4 receptor on the motor nerve stump, promotes axonal re‐growth and neurotransmission rescue. Of note, a chemical agonist of CXCR4 stimulates nerve regeneration in several conditions, recapitulating CXCL12α action (Negro et al, 2019 , Zanetti et al, 2019 ; Stazi et al, 2020 ).…”
Section: Methods To Study Schwann Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, therapeutic interventions may be directed towards improving the regenerative capacity of affected tissues and cells. This is the case of NUCC-390, an agonist of CXCR 4 receptor, which promotes the regeneration of nerve terminals affected by neurotoxic PLA 2 s that act presynaptically [ 115 ], or possible therapies to improve skeletal muscle regeneration after venom-induced myonecrosis [ 116 , 117 ]. Hence, the in depth understanding of venom composition, the mechanisms of action of the most relevant toxins, and the pathophysiology of envenomings will provide valuable information not only for the design of specific toxin inhibitors, but also for other interventions aimed at controlling endogenous pathways playing a role in envenoming.…”
Section: Beyond the Direct Action Of Toxins: The Need To Further Understand The Pathophysiology Of Envenoming In The Search For Novel Thementioning
confidence: 99%
“…Then, isolation of the NMJs and sequencing of their RNA provided a time-resolved mRNA profiling of the NMJ during the entire process of degeneration and regeneration [15]. By this approach, we found that the molecular axis composed by the chemokine CXCL12α and its receptor CXCR4 acts as a potent driver of MAT regeneration [15], and that the small molecule compound NUCC-390, an agonist of CXCR4 [16], is a strong promoter of nerve regeneration in several models of PNS damage, spanning from neurotoxic venoms to traumas [17][18][19].…”
Section: Introductionmentioning
confidence: 99%